Exploring mistreatment of women during childbirth in a peri-urban setting in Kenya: experiences and perceptions of women and healthcare providers - Jackline Oluoch-Aridi; Vania Smith-Oka; Ellyn Milan; Robert Dowd (Reproductive Health, 2018)
Abstract Background In Kenya, indirectly caused maternal deaths form a significant portion of all maternal deaths within the health system. Many of these deaths are avoidable and occur during delivery and labor. Poor quality health service has been a recurring concern among women in Kenya, with women reporting interactions with healthcare workers that are often demeaning and abusive. This paper explores the experiences and perceptions of both female patients and healthcare workers regarding mistreatment during childbirth. This study aims to provide recommendations on how dignified care can be made the norm, specifically focusing on a peri-urban setting in Kenya. Methods The research was accomplished using qualitative research methods with focus group discussions and in depth interviews with women and healthcare workers. The aim was to gain a deeper understanding of the manifestations of mistreatment within the context of a peri-urban setting in Kenya. Results Female patients reported different forms of mistreatment, such as verbal abuse, physical abuse, neglect, discrimination, abandonment, poor rapport and failure of the health system to uphold professional standards. The healthcare workers described a health system that was weak and fragmented with poor policy support particularly for the new free maternity services policy leading to the mistreatment of women. Conclusion Newly formed County Governments need to provide resources for a functioning health system to ensure an enabling environment for the provision of high quality maternal health services. This process can include feedback loops with maternity clients to ensure woman-centered services. Policy makers need to strengthen oversight for the implementation of the free maternity services Community health volunteers can be trained to provide this information. Professional associations that govern the standards of quality care for healthcare workers need to address the mistreatment through retraining and norms transformation.